Capacity distributions in spatial stochastic models for telecommunications networks - Voss, Florian (Image analysis and stereology, 2009)
We consider the stochastic subscriber line model as a spatial stochastic modelfor telecommunication networks and we are interested in the evaluation ofthe required capacities at different locations of the network in order to provide, in fine, an estimation of the cable system which has to be installed.In particular, we consider hierarchical telecommunication networks with higher-level components (HLC) and lower-level components (LLC) located onthe road system underlying the network. The cable paths are modeled by shortest paths along the edge set of a stationary random tessellation, whereasboth HLC and LLC are modeled by Cox processes concentrated on the edgesof this tessellation. We then introduce the notion of capacity which depends on the length of some subtree on the edge set of the underlying tessellation. Moreover, we investigate estimators for the density and disiribution function of the typical length of this subtree which can be computed based on Monte Carlo simularions of the typical serving zone. In a numerical study, the density of the typical subtree length is determined for different specific models.
Keywords: telecommunication; telekomunikacije; stohastični modeli